Perancangan Sistem Informasi Pengelolaan Akun Pada Aplikasi SAP dengan Metode Waterfall - Hamdan Zulfa Rais; Dimas Febriawan (Bulletin of Computer Science Research, 2025)
The need for an account management application in the SAP system is crucial for maintaining the reliability of annual audit trails, which are an essential part of corporate data governance. This application is designed to facilitate access rights management and record every user activity within the SAP system, aiming to ensure the integrity and security of company data. Without a robust system for managing access rights and monitoring user activity, audit trails become vulnerable to risks such as data misuse, shifting of responsibilities, and invalid user credentials. This can lead to financial and reputational losses for the company. This research aims to design and build an effective SAP system account management application to enhance audit trail reliability and minimize risks that can occur in the SAP system's account management process. A good information system will enable companies to manage and secure data more effectively, support license audits, and meet applicable compliance standards. The Waterfall method is used to achieve these objectives, encompassing requirements analysis, system design, implementation, testing, and maintenance phases. Through this approach, the expected outcome is an SAP account management application that is effective, secure, and supports audit standards as well as corporate data security governance.